Thomas Kent letter to Pam Allen regarding Greater Scaup sighting, June 22, 1994 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1994)
Letter from Thomas Kent to Pam Allen dated June 22, 1994. In this letter Kent explains that the reason a Greater Scaup sighting wasn't included in the Fall report was because of the early date, the difficulty of identification, and the lack of collaborating reports. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed